Revision of Argoravinia Townsend (Diptera: Sarcophagidae) of Brazil with the description of two new species - Da Silva Carvalho Filho, Fernando; Esposito, Maria Cristina (Zootaxa, 2012)
The genus Argoravinia Townsend comprises six species restricted to the New World, with the exception of two speciesintroduced into the Marshall Islands. The nominal genus Raviniopsis Townsend was considered a junior synonym of Ar-goravinia in the last catalogue of Sarcophagidae and the results of the present study support this arrangement. However,Argoravinia (s.s.) and Raviniopsis are considered as subgenera of Argoravinia, since they comprise two distinct speciesgroups that are each inferred to be monophyletic based on characters of the male and female terminalia. Four species ofArgoravinia previously recorded from Brazil are redescribed: A. alvarengai Lopes, A. aurea (Townsend), A. brasiliana(Lopes), and A. rufiventris (Wiedemann). Two new species of the subgenus Argoravinia are described from the BrazilianAmazon: A. catiae sp. nov. and A. paraensis sp. nov. Additional information on the biology of A. aurea is provided. A key to all six described species of Argoravinia is presented.